AI-enabled foraging in the forest: disrupting efficiency-driven sociotechnical imaginaries in wild foraging - Oostveen, Anne-Marie; Fletcher, Sarah R. (Springer, 2026)
This paper examines the social, ethical, and governance implications of introducing AI- and drone-based automation into wild berry foraging in Finland. Drawing on expert interviews and Science and Technology Studies (STS), particularly sociotechnical imaginaries and co-production, it focuses on an efficiency-driven imaginary embedded in the FEROX project, where automation and data-driven optimisation are positioned as solutions to labour shortages and underutilised forest resources. Rather than analysing this imaginary in isolation, the paper shows how it becomes disrupted when confronted with shifting labour conditions, cultural practices, and environmental values. Interview findings from foragers, engineers, ethicists, and forest scientists reveal how AI-enabled technologies intersect with existing socioecological dynamics in ways that generate tension and contestation. In particular, recent restrictions on seasonal migrant labour expose the fragility of assumptions underpinning the system, while local traditions, ecological ethics, and concerns about surveillance and data governance challenge efficiency-oriented approaches to automation. The paper argues that AI-enabled foraging technologies are not neutral tools but are shaped by, and reshape, the social and ecological contexts in which they are deployed. By foregrounding these tensions, it calls for participatory, culturally informed, and ecologically sensitive approaches to AI design and governance in natural resource settings.
Keywords: Sociotechnical imaginaries; AI governance; Automation and labour; Environmental AI; Ecological practices; 46 Information and Computing Sciences; 50 Philosophy and Religious Studies; Generic health relevance; Artificial Intelligence & Image Processing; 4608 Human-centred computing; 5001 Applied ethics; 5003 Philosophy